Overview of Foot Care For Diabetes Mellitus Patients in The Work Area Gondangrejo Public Health Center Karanganyar - Septi Watik Nurhidayah; Ida Nur Imamah (Lembaga Pengembangan Kinerja Dosen, 2026)
Foot care is an essential aspect of preventing diabetes mellitus complications, especially diabetic ulcers that can lead to amputation. However, foot care practices among individuals with diabetes mellitus remain low. Objective; to describe foot care practices among individuals with diabetes mellitus in the working area of ​​Gondangrejo public health center, Karanganyar. Method; this study used a descriptive quantitative design. The population consisted of all diabetes mellitus patients enrolled in the prolanis program, totaling 82 people. Samples were selected using an accidental sampling technique, with 45 respondents participating. The research instrument used the Nothingham assessment of functional foot care (NAFF) questionnaire, which has been tested for validity and reliability. Results; Most respondents were over 45 years old, female, had completed elementary school, and were employed. The majority had suffered from diabetes for 1-5 years. Foot care behavior was mostly in the poor category (80%). Conclusion; The majority of diabetes mellitus patients in the Gondangrejo public health center area demonstrated poor foot care practices.